1989
DOI: 10.1126/science.2911720
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Meaning of the Kingdom Concept: an Unusual Ribosomal RNA from Giardia lamblia

Abstract: An analysis of the small subunit ribosomal RNA (16S-like rRNA) from the protozoan Giardia lamblia provided a new perspective on the evolution of nucleated cells. Evolutionary distances estimated from sequence comparisons between the 16S-like rRNAs of Giardia lamblia and other eukaryotes exceed similar estimates of evolutionary diversity between archaebacteria and eubacteria and challenge the phylogenetic significance of multiple eukaryotic kingdoms. The Giardia lamblia 16S-like rRNA has retained many of the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
376
2
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(393 citation statements)
references
References 14 publications
13
376
2
2
Order By: Relevance
“…Earlier phylogenetic analyses indicated that diplomonads (including G. intestinalis) are among the deepest divergences in the eukaryotic lineage and the tree was (EAL73658); Gi Dcl1 G. intestinalis Dcl1 (AAO17549); Hs Dcr1 H. sapiens Dcr1 (NP_803187); Ps Dcl1 P. sojae Dcl1 (v1_C_860007 at http://www.genome.jgi-psf.org/sojae1/sojae1. home.html ); Spo Dcr1 S. pombe Dcr1 (Q09884); Tt Dcr2 T. thermophila Dcr2 (BAD34723) "rooted" with these mitochondrion-lacking unicellular eukaryotes (Sogin et al 1989;Sogin 1991). Recent studies have suggested that this rooting may have been patterned by methodological artefacts (Philippe et al 2000).…”
Section: Phylogeny Of Argonaute-piwi Dicer-like and Rdrp Proteinsmentioning
confidence: 99%
“…Earlier phylogenetic analyses indicated that diplomonads (including G. intestinalis) are among the deepest divergences in the eukaryotic lineage and the tree was (EAL73658); Gi Dcl1 G. intestinalis Dcl1 (AAO17549); Hs Dcr1 H. sapiens Dcr1 (NP_803187); Ps Dcl1 P. sojae Dcl1 (v1_C_860007 at http://www.genome.jgi-psf.org/sojae1/sojae1. home.html ); Spo Dcr1 S. pombe Dcr1 (Q09884); Tt Dcr2 T. thermophila Dcr2 (BAD34723) "rooted" with these mitochondrion-lacking unicellular eukaryotes (Sogin et al 1989;Sogin 1991). Recent studies have suggested that this rooting may have been patterned by methodological artefacts (Philippe et al 2000).…”
Section: Phylogeny Of Argonaute-piwi Dicer-like and Rdrp Proteinsmentioning
confidence: 99%
“…The typical applications of these loci have therefore varied accordingly. For Giardia the conserved SSU rDNA is traditionally used for species and assemblage/subassemblage level genotyping (Sogin et al 1989 ;van Keulen et al 1991van Keulen et al , 1993van Keulen et al , 1995Hopkins et al 1997), where as the most variable locus, tpi, is frequently used for subtyping clinical samples (Lu et al 1998 ;Amar et al 2002) and the gdh locus, with a substitution rate midway between them, has a broad application spectrum (Monis et al 1996(Monis et al , 1999.…”
Section: Consensus Sequence Substitutionsmentioning
confidence: 99%
“…(1) Thompson et al (2000), (2) Sogin et al (1989), (3) van Keulen et al (1995), (4) Not yet published, Xiao, S., South China Agricultural University, 2005, (5) Healey et al (1990), (6) , (7) Monis et al (1999), (8) (2000), (20) Yee and Dennis (1992), (21) Ey et al (1997), (22) Leonhard et al (2006), (23) Monis et al (1996), (24) Ey, P., University of Adelaide, 2002, submitted as a set with those from Ey et al (1997), (25) , (26) Itagaki et al (2005), (27) Matsubayashi et al (2005), (28) Robertson et al (2006), (29) Mowatt et al (1994), (30) Trout et al (2003), (31) Baruch et al (1996), (32) Sulaiman et al (2003), (33) Sulaiman et al (2004), (34) Not yet published, Mowatt, M., National…”
mentioning
confidence: 99%
“…ADP/ATP carrier orthologs from plants, yeast and chordates are all highly similar to one another (28), whereas the HMSC is only modestly similar to any superfamily member in any of those taxa (not shown). Ciliates, plants, fungi and chordates are felt all to have diverged from one another more or less at the same time, judged from evolutionary distances between small subunit ribosomal RNA sequences (32,33,34). This implies that the HMSC gene must have diverged from the known carrier genes well before that radiation, and therefore is not orthologous to any of them.…”
Section: Polyadenylation Sitesmentioning
confidence: 99%